Implementation of Learnig Corners as a Dynamic tool to Teach ESL for Kindergarden Students - Castro Corrales, Zury Sadai (UDELAS, 2019)
Learning corner activities are very import in education for students from initial education. Tn this work, we will refer to learning corners as dynamic tools to teach ESL. which consists of three chapters. In so doing we will address various issues such as its definition, utility, organization, and methodology. The benefit of this tool depends on the abilities and skills that the teachers who must work with children from 4 to 5 years of age during the development process an strengthening of their intellectual and motor skills. Through this project we will implement the importance of learning corners for the teacher in the teaching-learning process. Creative and imaginative learning implies that the chil can manipulate experiments and discover their potential for good learning inside and outside the school. By implementing the learning corners, the use of teaching resource for teaching is optimized through a pedagogical and methodological proposal. Also, learning goes from being sedentary to active learning, children become protagonistis of their own formation in an integral way by creating a playful environment and allowing a relatins hip in a dynamic, active, an participatory way. This project thefore demonstrates features, techniques and materials that we need to buil a learning corner as a flexible resource.